Contrato de fiança: alternativas para o fiador na locação imobiliária em face do locador desleal - Oliveira, Laura Virgínia Morais de (2017)
The present work has the scope to identify a legal solution for the guarantor when the lessee-secured is not paying rent on the lease of the property and the landlord is inert to promote the relevant action of eviction in the face of the tenant. The choice of problem arose from the finding that the guarantor, in many real estate leasing contracts, becomes the hostage of an indigent landlord, and may jeopardize all of his assets. This is essentially a bibliographical research. The eviction action is the fastest way for the landlord or landlord to resume the property of the defaulting tenant, however, the guarantor is not allowed the extraordinary legitimacy to promote the eviction action in the face of the tenant-debtor. However, the guarantor may file a contract termination action for breach of contract in the face of the unfair landlord since he did not observe the lateral duties or annexes derived from the principle of objective good faith and thus to fulfill the guarantee provided or when demanded by the landlord can argue the exception of the contract not fulfilled, as the disrespect to the lateral duties is a modality of contractual default.